MANAGEMENT EFFORTS TO INCREASE PEOPLES INTEREST IN READING ON THE TAMAN BACA MASYARAKAT (TBM) IN PKBM SEKECAMATAN TAMPAN KOTA PEKANBARU - Karmanto Karmanto; Titi Maemunaty; Widiastuti Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Research it is based on the state of management increase peoples interest in reading. Because efforts management increase peoples interest in reading on the Taman Baca Masyarakat (TBM) in PKBM Sekecamatan Tampan Kota Pekanbaru. The formulation of a problem of this research is how high management efforts to increase peoples interest in reading on the Taman Baca Masyarakat (TBM) in PKBM Sekecamatan Tampan Kota Pekanbaru?. The purpose of this research is to find management efforts to increase peoples interest in reading on the Taman Baca Masyarakat (TBM) in PKBM Sekecamatan Tampan Kota Pekanbaru. The population in research has reached 52 people. So research sample areas 32 people and the other 20 a test sample of trying to, simple sample that is used is the simple sampling jenuh. An instrument data collection the survey with 54 a statement and if the trial live 49 statement valid for made instrument in research. Data analysis through descriptive analysis quantitative. The research management efforts to increase peoples interest in reading on the Taman Baca Masyarakat (TBM) in PKBM Sekecamatan Tampan Kota Pekanbaru considered to be high, with the percentage of (SB+B) 70% on indicators of the quality of taking the responsible toward take over as coach of through the observance of aturan-aturan which have already been stipulated. While the lowest is with a percentage (SB+B) 62% in their indicators regarding the development of science and technology.Key words: Management efforts, Management efforts to increase peoples interest in reading